More dream homes 100 inspirational interiors - Einsiedel, Andreas; Thornycroft, Johanna (London Merrell, 2012)
A companion and successor to the hugely successful 'Dream Homes', this book presents an entirely new selection of 100 stunning interiors of all styles from around the globe. It describes concisely the key characteristics of each home and how these have been achieved, providing insights into the work of leading interior designers
Originally published: 2008
2 13
Keywords: Interior decoration